Sustainable energy recovery from municipal solid wastes: An in-depth analysis of waste-to-energy technologies and their environmental implications in India - Ravinder Kumar; Shubham Sharma; Abhinav Kumar; Rajesh Singh; Fuad A. Awwad; M. Ijaz Khan; Emad A. A. Ismail (Energy Exploration & Exploitation)
In recent years, in response to an increased demand for renewable energy sources, there has been a rise in the rate of energy recovery from municipal solid trash. This study analyses the feasibility of employing a variety of energy recovery methods to produce clean power from municipal solid waste (MSW). The conversion of MSW into a variety of useable sources of energy, such as fuel, heat and electricity, is required for the process of energy recovery. Other strategies for the recuperation of lost energy include gasification, incineration, anaerobic digestion, and the recovery of landfill gas. This article provides a high-level assessment of the advantages and disadvantages associated with each technology that is currently being utilised in India. According to the findings of the study, recovering energy from municipal solid waste is a sustainable and cost-effective option that can fulfil the growing demand for power while simultaneously lowering emissions of greenhouse gases and the amount of rubbish that ends up in landfills.